Fermentative characteristics, agronomic evaluation, and microbial populations of sorghum silage with additives - Tiago Venturini; Marcela Abbado Neres; Rodrigo Cesar dos Reis Tinini; Jéssica Gabi Dessbessell; Pâmela Rosana Schneider; Cibele Regina Schneider; Luana Muxfeldt; Andressa Radtke Baungratz; Maria Luiza Fischer; Maximiliane Alavarse Zambom (Pesquisa Agropecuária Brasileira)
Abstract The objective of this work was to evaluate the effects of the use of additives on the ensiling of AGRI 002E sorghum (Sorghum bicolor), focusing on the chemical composition, loss, microbial profile, and fermentative stability of the fodder. Sorghum was harvested 111 days after sowing, chopped, and ensiled in PVC silos under different treatments, as follows: without additives (SS), with inoculant (SSI), with urea (SSU), and with urea and inoculant (SSUI). The silos were opened and analyzed at 1, 3, 7, 14, 28, and 56 days after ensiling. The inclusion of urea and bacterial inoculant did not significantly affect dry matter content, but influenced dry matter recovery and microbial population, reducing the presence of clostridia and fungi. Dry matter and gas losses were minimal, indicating an adequate fermentation. The additives contribute to a more stable fermentation and a better preservation of the ensiled material, particularly by reducing undesirable microbial populations.